Health Behavior Of Coastal Communities In Percut Sei Tuan Sub-Distric - Agustina, Dewi; Ainy Kusuma, Nabilla Tawaqal; Wulandari, Nabila; Oktapianti, Wanda Aulia; Khairani, Khovifah; Syahadah, Rahmah Fadillatu; Ujung, Sofia Rahma (Sean Institute, 2024)
Public health is an important part of maintaining local health. This study was conducted to describe public health behavior in Percut Village, Percut Sei Tuan District, Deli Serdang Regency. The research method used is a descriptive research method using observational data collection methods, questionnaires and in-depth interviews. Research shows that access to health and hygiene services is poor in coastal communities, but awareness of the importance of health is increasing. Socioeconomic factors also influence people's perception of health, including better eating habits, adequate physical activity, and adequate rest are also seen. This study provides an in-depth picture of the health condition of the coastal communities of Percut Village and provides a basis for the development of better health programs in the region.